Critical Discourse Analysis of Pakistani Drama "Ranjha Ranjha Kardi" - Rehman, Hurria; Rafi, Arooj; Baig, Sana (Pakistan Languages and Humanities Review, 2024)
Critical discourse analysis (CDA) is a breakdown of interactive or transactional communication. It enables the understanding of the message conveyed through different media through linguistic analysis. This provides the basis for either deductive or inductive reasoning. It justifies various genres of text, allows for liberating linguistics and creativity in all its forms. It reinforces the ways in which language users use language to communicate with power dynamics in mind. The purpose of this study is to explore the use of CDA (Critical Discourse Analysis) to investigate the need for such drama in Pakistani society to combat the stereotypes and stigma attached to the portrayal of mental illness. Based on the framework of "Critical Discourse Analysis" (CDA), the study hypothesizes that the issue is again power relations, the propaganda we are part of about mental illness, the distortion of the facts, the story created by the media that third world countries are bad — sensing their marginalized communities through the media. The prejudice and stereotypical behaviour exists towards people with disabilities whether physical or mental.